Hubungan Tingkat Pengetahuan dan Sikap dengan Tindakan Pencegahan Penularan HIV/AIDS pada Remaja di SMA PGRI 3 Wilayah Kerja Seberang Padang - Ilva Yulistisia; Defia Roza; Yosi Suryalinilsih; Tasman Tasman; Hendri Budi (Jurusan Keperawatan Mandiri Poltekkes Kemenkes Padang, 2023)
The number of HIV positive cases reported in Indonesia from year to year tends to increase. The number of HIV cases in 2021 increased by 76 people and since 2022 there have been 3 new cases of HIV/AIDS. Where the highest cases were in their teens, the results of interviews conducted indicated that there were cases of immoral acts. Results The aim of this study was to determine the relationship between knowledge, attitude and prevention of HIV/AIDS transmission in PGRI 3 high school youth in the Seberang Padang Working Area in 2022. This type of research used a quantitative research method. The research design used was a cross sectional study. This research was conducted in January - June 2022. For data collection in this study, it was conducted from June 6 2022 to June 11 2022. The population in this study were all students at SMA PGRI 3 Seberang Padang with a total of 100 people. The sampling technique in this study is total sampling. The results showed that the low level of knowledge about HIV/AIDS in adolescents was close to half (46%), close to half (42%) of adolescents had a negative attitude towards HIV/AIDS, whereas in the prevention of HIV/AIDS transmission that was close to half (46%) having preventive measures against the transmission of HIV/AIDS is not good. The results of the study show that the statistical test has a Sig.(p) value of 0.019 which is less than 0.05. The statistical test shows a Sig.(p) value of 0.007 which is less than 0.05. There is a relationship between the two variables. The suggestion for this research is for adolescents to increase their knowledge and insight about HIV/AIDS so that the risk of HIV/AIDS can be avoided.